PENGARUH PENGEMBANGAN PEGAWAI TERHADAP EFEKTIFITAS KERJA PEGAWAI PADA KANTOR SEKRETARIAT DAERAH KOTA SIBOLGA - M. Husni Thamrin Nasution, Ossy Memorial R (PERSPEKTIF, 2016)
Organization is a formal system that consist of two or more people which cooperating to complete a specific goal. Management which is a tool to reach that goal consist of 6 (six) element, which is men, money, method, materials, machines and market. Human is the most important element because human control the other 6(six) elements. Education, training and job promotions are the important element in improving the effectiveness of work. Education and training is the organization learning process in order to imptove the competence of candidates for civil servants and civil servants itself. While job promotion is an important role for each emplotee, because the presence of job promotion means there is a recognition of the abilities and skills of the employee to occupy a higher position. The conclusion states that the education and training and promotions are simultaneously influence the work effectiveness of an employee at Sibolga Secretariat Office. It makes clear that education and training and promotions largely determines the work efficiency and effectiveness of working employee at Sibolga Secretary Office.